PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI MA MIFTAHUL HIDAYAH - Frida Rohmatika; Risnawati; M. Fikri Hamdani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to enhance students' curiosity, focus, teamwork, and motivation. By creating challenging problems, this model can increase students' interest in solving them. The method used in this research is quantitative, focusing on statistical data analysis. The hypothesis proposed is that there is an influence of the problem-based learning model on students' learning motivation. The research sample consists of 40 tenth-grade students, selected using random sampling techniques. The data analysis tools include validity tests, reliability tests, normality tests, as well as simple linear regression analysis, determination tests, and t-tests. The results of the simple linear regression analysis show the regression equation Y = 14.803 + 0.906 X, indicating that the application of the problem-based learning model has an influence of 0.906 on students' learning motivation. From the determination test, an R Square value of 84.0% was obtained, and the t-test results show that the calculated t-value is greater than the table t-value (14.144 > 1.667). Therefore, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. This indicates that the problem-based learning model has a positive effect on students' learning motivation.